Ergodicity of Stochastic Burgers’ System with Dissipative Term - Guoli Zhou; Boling Guo; Daiwen Huang; Yongqian Han (Abstract and Applied Analysis, 2013)
A 2-dimensional stochastic Burgers equation with dissipative term perturbed by Wiener noise is considered. The aim is to prove the well-posedness, existence, and uniqueness of invariant measure as well as strong law of large numbers and convergence to equilibrium.